Perspectives and experiences of researchers regarding feedback of incidental genomic research findings: A qualitative study - Joseph Ochieng; Betty Kwagala; John Barugahare; Erisa Mwaka; Deborah Ekusai-Sebatta; Joseph Ali; Nelson K. Sewankambo (PLoS ONE, 2022)
Background There is a plethora of unanswered ethical questions about sharing incidental findings in genetics and genomics research. Yet understanding and addressing such issues is necessary for communicating incidental findings with participants. We explored researchers’ perspectives and experiences regarding feedback of incidental genomics findings to participants. Methods This was a qualitative study using semi-structured interview schedules for In-depth interviews. Thirty respondents were purposively selected based on role as genetics and genomics researchers in Uganda. Data were analysed through content analysis to identify emerging themes using a comprehensive thematic matrix. QSR International NVivo software was used to support data analysis. Results a). On perceptions, sharing of incidental findings was acceptable and four themes emerged including role of professional judgement; role of ethics committees and ethical guidelines; optimal disclosure practices; limits to professional duty and uncertainty and; b). on practices, sharing had been carried out by some researchers and a theme on experience and practices emerged. Conclusion Feedback of incidental genomics research findings to participants is generally acceptable to researchers. Some researchers. Challenges include lack of ethical guidelines and uncertainty about the findings.